2020
DOI: 10.1002/aelm.201901162
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent‐Neodymium Additive Modulated MAPbBr3 Perovskite Nucleation and Growth: Ultrawide Processing Window for One‐Step Fabrication of Efficient Light‐Emitting Perovskites

Abstract: Hybrid metal halide perovskite–based light‐emitting diodes and lasers have demonstrated outstanding performance and currently lead a new trend in the optoelectronic field; however, the widely used one‐step spin‐coating method assisted by an antisolvent suffers from the narrow processing window of antisolvents, which limits its further use in commercial applications. The present work incorporates trivalent‐neodymium ions (Nd3+) into methylammonium lead tribromide (MAPbBr3) perovskite thin films to control nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Meanwhile, the carrier densities are evaluated as 1.404 × 10 19 cm −3 for CsPbI 3 PQDs and 1.621 × 10 19 cm −3 for CsPbI 3 : Er 3+ (7.7%) PQDs. It is found that the effect reduces the trap density and increases the carrier densities of PQDs after Er 3+ doping, similar to the previous literatures 49 , 50 .…”
Section: Resultssupporting
confidence: 91%
“…Meanwhile, the carrier densities are evaluated as 1.404 × 10 19 cm −3 for CsPbI 3 PQDs and 1.621 × 10 19 cm −3 for CsPbI 3 : Er 3+ (7.7%) PQDs. It is found that the effect reduces the trap density and increases the carrier densities of PQDs after Er 3+ doping, similar to the previous literatures 49 , 50 .…”
Section: Resultssupporting
confidence: 91%
“…Many strategies have been implemented to maximize the PLQY of perovskites, such as defect passivation, metal ion doping, and crystal quality improvement by controlling crystal growth. [81][82][83][84] In addition, the different effects caused by k 1 and k 3 are primarily reflected in the high carrier density, corresponding to the high current density of LEDs. Figure 2d shows that at a high carrier density, the attenuation trend of PLQY is highly coincident and has a weak dependence on k 1 .…”
Section: Carrier Recombinationmentioning
confidence: 99%
“…These additives tend to interact with precursor solute in solution, promoting the heterogeneous nucleation of the perovskite, which help to extend the perovskite processing window. In the process of fabricating MAPbBr 3 film in dichloromethane, Zhang et al incorporated trivalent neodymium ions (Nd 3+ ) into perovskite thin precursor to control nucleation and crystal growth [105]. These pre-nucleated crystals in perovskite precursor make them less sensitive to rapid changes in the solvent environment during the high-speed rotation process, thus resulting in widening the processing window from 3-5 to 18 s (Figure 5(a)).…”
Section: Precursor Additivesmentioning
confidence: 99%
“…Therefore, the high reproducibility of high-quality perovskite films was attributable to 18C6 effectively suppressing the generation of 2H phase perovskites.
Figure 5. (a) Schematic diagrams of the process of preparing MAPbBr 3 perovskite film via the antisolvent method and use of an Nd 3+ additive, and schematic diagrams of the nucleation process and crystal growth. Reprinted from [105] with permission. (b) Schematic diagram of the deposition process of perovskite films without and with 18C6.
…”
Section: Precursor-solvent Engineering For Widening the Processing Wi...mentioning
confidence: 99%